Implementation of Project Management Standards and Project Success: The Mediating Role of the Project Management Office - Amjad Pirotti; F. A. Mohd Rahim; Norhanim Zakaria (Journal of Engineering, Project, and Production Management, 2022)
This research puts the spotlight on the implementation of project management standards, project management body of knowledge (PMBOK) 10 knowledge areas, in Iranian construction project-based organizations considering the significant role of the project management offices (PMOs) and to the extent to which that leads to project success. The objectives of this research are; to examine the influence of project management standards on project success, and to investigate the impact of PMO as a mediator between project management standards and project success in construction project-based organizations in Iran. Having the knowledge and research gap unfolded, a conceptual framework proposed to bridge the gap and three hypotheses were developed based on the study objectives. A survey, targeting Iranian project managers and construction practitioners working in grade 1 construction companies, was conducted and multivariate analysis techniques were adopted to analyze the data. After the exploratory and confirmatory factor analyses, the SEM analysis was used to test the hypothesized relationships. In general, the developed conceptual framework was confirmed, and the analysis enhanced the understanding of the current status of project management standard implementation and construction industry practitioners' perception of the factors contributing to project success.